Real-World Outcomes of Anti-VEGF Treatment for Retinal Vein Occlusion in Portugal. Issue 6 (8th November 2017) - Vaz-Pereira, Sara; Marques, Inês P.; Matias, João; Mira, Filipe; Ribeiro, Lígia; Flores, Rita
Purpose: Retinal vein occlusion (RVO) is an important cause of visual disability in the modern world. We aim to evaluate the real-world outcomes of patients with RVO treated with anti-vascular endothelial growth factor (VEGF) in Portugal. Methods: We performed a retrospective, observational, multicenter study including 8 centers across Portugal and 200 patients treated with either ranibizumab or bevacizumab. Data were collected at 3 time points: time of diagnosis (0 time point) and 6 and 12 months after initiating treatment. Demographic and clinical data were collected. Results: Median visual acuity (VA) and central macular thickness (CMT) improved in the branch RVO (BRVO), central RVO (CRVO), bevacizumab, and ranibizumab groups at 6 and 12 months compared to baseline, with CMT improving further only in the CRVO and ranibizumab groups between 6 and 12 months (p = 0.002 and p = 0.001, respectively). The CMT was lower in the ranibizumab group compared to the bevacizumab group both at 6 and 12 months (p<0.02). Median CMT improved in both the good and poor baseline VA groups at 6 and 12 months compared to baseline (p<0.001). Median VA only improved for the group with poor baseline VA at 6 and 12 months of follow-up (p<0.001). Regression analysis identified several baseline variables as predictors of visual outcomes at 6 and 12 months, with different results depending on the analyzed group. Conclusions: Both treatments were effective, although less effective than results reported in clinical trials. The morphologic response was better with ranibizumab compared to bevacizumab, although functionally there were no differences.